PEMBERDAYAN MASYARAKAT DALAM PENGELOLAAN SAMPAH PLASTIK MENJADI BUNGA ANGGREK - Adrianus Varman; Maria Salviana Nita; Maria Susanti Stefani; Katarina Vieschi Limu; Velisitas Yolenta Wati; Fabiola Anjela; Emiliani Erentrudis Mbela (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
These community service activities are implemented to improve the skills of the public in processing plastic waste. A common problem experienced by the community is a lack of understanding in using plastic waste and the dangers that will occur if the society does not wisely process its household waste. This leads to waste and environmental damage. This activity also aims to provide education, mentoring, and hands-on practice to the community about plastic waste utilization. The method used in this activity is to use a participatory approach. Where this approach involves the public directly in the activities of PKM. From the activities of PKM carried out by students together with the community produce one ornamental flower orchid from plastic waste.